Dangerous dancehall reggae and Caribbean treaty obligations - Ewart, Andrea M. (2012)
Argues that Jamaica and / or its artistes should seek from the Caribbean Court of Justice (CCJ), an interpretation and correct application of the public moral / public order exceptions to the rights granted under the Revised Treaty as Jamaican dancehall artistes are being arbitrarily denied their right to freedom of movement and to provide their services within the region.